Mechanisms of genuine humic acid evolution and its dynamic interaction with methane production in anaerobic digestion processes - Wang, Xiqing; Muhmood, Atif; Lyu, Tao; Dong, Renjie; Liu, Hongtao; Wu, Shubiao (Elsevier, 2020)
Humic acid (HA), a byproduct formed during the biological conversion of organic matter into biogas in the anaerobic digestion (AD) process, contains complex structures and redox functions. However, the evolution mechanism of HA and its interaction with CH4 production during the AD process have not been fully explored, particularly with respect to various substrates and temperature conditions. In this study, we investigated the evolutionary dynamics of the structure and function of genuine HA that naturally formed in the AD processes of chicken manure and corn stover under mesophilic (37 °C) and thermophilic (55 °C) conditions. The results demonstrated that the HA evolution mechanisms in AD of chicken manure and corn stover have different pathways. The AD of core stover showed higher degree of aromaticity (41.2–66.7% and 45.3–68.4% for mesophilic and thermophilic respectively) and humification index (1.5–4.2 and 2.8–4.5 for mesophilic and thermophilic respectively) than those (28.3–45.3% and 30.2–54.5% of aromaticity and 0.6–1.2 and 1.3–3.7 of humification index) in AD of chicken manure. The results from HSQC NMR spectroscopy and 2D-COS-FTIR spectroscopy demonstrated an accelerating effect of the higher temperature on the evolution of HA through humification. Moreover, the concurrent decomposition and re-polymerization of HA during both AD processes, resulting in positive and negative effects on CH4 production in the fast and slow CH4 production stages, respectively. The dynamic interaction was due to variations in the electron transferring ability and structure of the formed HA. The results could not only advance our understanding of the mechanisms of HA evolution and its interaction with the performance of AD process, but also support further research toward improving AD performance by regulating HA formation and transformation.
Keywords: Re-polymerization; Redox capacity; Humification; Humic substances; Biogas production